Family influences on health and nutrition practices of pregnant adolescents in Bangladesh. (9th July 2021) - Pike, Vanessa; Kaplan Ramage, Abigail; Bhardwaj, Anjali; Busch‐Hallen, Jennifer; Roche, Marion Leslie
Abstract: Adolescent pregnancy can result in serious risks to the mother and her baby; yet, adolescents are among the least likely to access healthcare. Specific nutrition or antenatal care (ANC) guidelines for supporting pregnant adolescents are not available. To understand experiences and decision‐making of pregnant adolescents in Bangladesh related to ANC and nutrition practices, peer interviewers were trained to conduct qualitative interviews in Dhaka and Rangpur with pregnant adolescents ( n  = 48), adolescent mothers ( n  = 48), adolescents' family members ( n  = 64) and health service providers ( n  = 32). Key themes explored included perception and support of adolescent pregnancy, experiences in seeking ANC, dietary practices, sources of information and roles of male and female family members. Spheres of influence on adolescent pregnancy were identified through analytical framework informed by the socio‐ecological model. Respondents felt that adolescent pregnancy is risky and that adolescents require support and guidance through this experience. Families were highly influential on the care seeking, health and nutrition of pregnant adolescents, and mothers/mothers‐in‐law primarily took on the decision‐making roles, with husbands actively participating. Adolescents valued family support but felt a loss of autonomy and agency upon becoming pregnant. Financial constraints were the greatest perceived barrier to appropriate nutrition and healthcare; yet, both were valued. There is sometimes discord of health and nutrition beliefs between families and health service providers; more research is needed to understand this further. It is essential to engage family members and adolescents in initiatives to increase access to quality ANC for pregnant adolescents, improve dietary practices and support the ability to delay pregnancy.